Preparation and optical properties of magnetic carbon/iron oxide hybrid dots. Issue 65 (23rd August 2017) - Hu, Yin; Wang, Ping; Bunker, Christopher E.; Teisl, Lindsay R.; Reibold, McIver; Yan, Sijia; Qian, Haijun; He, Dawei; Sun, Ya-Ping
Abstract : Carbon/Fe3 O4 hybrid dots are prepared for their optical properties in reference to those of neat carbon dots. Abstract : Carbon dots (CDots), generally defined as small carbon nanoparticles with various surface passivation schemes for bright and colorful fluorescence emissions, have emerged to represent a rapidly advancing and expanding research field. Building upon the basic structural configuration of CDots, iron oxides were introduced for both magnetic and fluorescence properties in the resulting hybrid dots, thus resulting in more capabilities beyond those of neat CDots. The carbon/Fe3 O4 hybrid dots with oligomeric polyethylene glycol or polyethyleneimine for surface functionalization and passivation were prepared in a facile thermal carbonization synthesis using microwave energy, coupled with magnetic separation. The magnetic hybrid dots were fluorescent over the visible spectrum, but the fluorescence quantum yields were found to be lower than those of their neat CDots counterparts, for which a possible quenching effect due to the Fe3 O4 in the dot structure was probed and evaluated. The results support the notion that the hybrid dot configuration could serve as a platform for imparting magnetic properties into brightly fluorescent CDots. Also investigated were the dot structures and compositions to gain a rough view of the carbon–iron oxide configurations in the hybrid dots. The application potential of the hybrid dots and opportunities for their further improvements are discussed.